2022
DOI: 10.22382/wfs-2022-13
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Based Prepreg For Composite Laminates

Abstract: A wood-based prepreg was formed using vacuum-assisted resin transfer molding (VARTM) and a low-viscosity thermoplastic resin. Wood strands were assembled to make a porous mat for resin injection. The resin filled most of the cavities inside the wood cells resulting in a void volume fraction of 7%. The Young's modulus and strength of the saturated wood strands were 38% and 124% higher, respectively, than those of wood strands prior to resin infusion. Flat laminates were produced by thermoforming prepreg plies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…In this sense, the tensile strength for the three-layer and four-layer composites were 43.8 MPa and 59.6 MPa, respectively. Those values were higher than the ones obtained by Mohammadabadi et al [6], who manufactured wood-based prepregs for composite laminates using wood strands and thermoplastic resin, obtaining a tensile strength of 32 MPa. However, the same authors also reported a higher tensile modulus (~13.40 GPa) than the ones obtained in this research (7.15 and 7.29 GPa).…”
Section: Mechanical Propertiescontrasting
confidence: 64%
See 4 more Smart Citations
“…In this sense, the tensile strength for the three-layer and four-layer composites were 43.8 MPa and 59.6 MPa, respectively. Those values were higher than the ones obtained by Mohammadabadi et al [6], who manufactured wood-based prepregs for composite laminates using wood strands and thermoplastic resin, obtaining a tensile strength of 32 MPa. However, the same authors also reported a higher tensile modulus (~13.40 GPa) than the ones obtained in this research (7.15 and 7.29 GPa).…”
Section: Mechanical Propertiescontrasting
confidence: 64%
“…Thus, in recent years, there has been an increasing interest in the development of prepregs that incorporate renewable and biodegradable materials. In this sense, sustainable materials, such as wood veneers [ 6 , 7 , 8 , 9 ] or natural fibers, as potential reinforcement materials in prepregs are being explored [ 10 , 11 , 12 ], offering benefits such as reduced environmental impact, increased biodegradability, and renewability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations